Labor Recruitment and Immigration in the Eastern North Carolina Food Industry - Griffith, David (The International Journal of Sociology of Agriculture and Food, 2012)
The food industry has been responsible for much of the immigration into North Carolina, with fruit and vegetable agriculture and factories for processing poultry, pickles, pork, and seafood central to the economies of the state’s eastern coastal corridor. Different sectors of the food industry, however, influence communities of the region differently and have varied influences on the communities from which immigrants come. This article compares three branches of North Carolina’s food industry – 1. poultry, pickle, and pork producers; 2. seafood producers; and 3. fresh fruit and vegetable producers – in terms of their labor recruitment methods and how those methods have influenced receiving and sending communities. It concludes with a brief consideration of the relationship between immigrants and new food movements oriented toward eating healthier, more locally, and more organically.